DGCR8 Promotes Neural Progenitor Expansion and Represses Neurogenesis in the Mouse Embryonic Neocortex - Hoffmann, Nadin; Weise, Stefan C.; Marinaro, Federica; Vogel, Tanja; De Pietri Tonelli, Davide (Frontiers in Neuroscience, 2018)
DGCR8 and DROSHA are the minimal functional core of the Microprocessor complex essential for biogenesis of canonical microRNAs and for the processing of other RNAs. Conditional deletion of Dgcr8 and Drosha in the murine telencephalon indicated that these proteins exert crucial functions in corticogenesis. The identification of mechanisms of DGCR8- or DROSHA-dependent regulation of gene expression in conditional knockout mice are often complicated by massive apoptosis. Here, to investigate DGCR8 functions on amplification/differentiation of neural progenitors cells (NPCs) in corticogenesis, we overexpress Dgcr8 in the mouse telencephalon, by in utero electroporation (IUEp). We find that DGCR8 promotes the expansion of NPC pools and represses neurogenesis, in absence of apoptosis, thus overcoming the usual limitations of Dgcr8 knockout-based approach. Interestingly, DGCR8 selectively promotes basal progenitor amplification at later developmental stages, entailing intriguing implications for neocortical expansion in evolution. Finally, despite a three- to five-fold increase of DGCR8 level in the mouse telencephalon, the composition, target preference and function of the DROSHA-dependent Microprocessor complex remain unaltered. Thus, we propose that DGCR8-dependent modulation of gene expression in corticogenesis is more complex than previously known, and possibly DROSHA-independent.